Uncovering Antibiotic Resistance Genes in Marmara Sea Mucilage via Shotgun Metagenome Sequencing - Gizem Karış; Herdem Aslan; Mehmet Hora; Aycan Gundogdu (Journal of Global Antimicrobial Resistance)
AIM: This study aims to uncover the composition of antibiotic resistance genes (ARGs) in the mucilage of the Marmara Sea using advanced shotgun metagenome sequencing techniques. BACKGROUND: The identification of antimicrobial resistance genes in the mucilage of the Marmara Sea, which reached alarming levels in 2021, is critical for assessing potential public health threats. METHOD: Mucilage samples were collected from 11 stations (Figure 1) between April and September 2021. Microbial DNA was isolated using commercial kits, and shotgun metagenome sequencing was conducted using an Illumina NextSeq-500 platform. The DNA data was analyzed using a de novo approach with IDBA-UD assembler, BWA-mem2, and Prodigal gene prediction algorithm. For ARG profiling, gene clusters were aligned to the CARD (The Comprehensive Antibiotic Resistance Database) using BlastX. RESULTS: The analysis revealed that sample MS8, with at least six different genes identified.MS3 contained four different resistance genes, and MS9 carried three. Additionally, the rsmA resistance gene was identified in samples MS10 and MS11. Sample MS7 contained both rsmA and VMB-1 resistance genes and MS5 contained rsmA and ErmB genes. No antimicrobial resistance genes were detected in MS2, MS4, and MS6. No sequencing data was obtained for MS1. CONCLUSIONS: Despite the high bacterial gene load, the antimicrobial resistance genes were relatively few and small. This may be due to the small size of contigs obtained after genome assembly or the predominance of environmental bacterial strains. This highlights the need for further studies to better understand the potential public health threats posed by mucilage